2022
DOI: 10.1002/cpt.2757
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Trastuzumab Deruxtecan on QT/QTc Interval and Pharmacokinetics in HER2‐Positive or HER2‐Low Metastatic/Unresectable Breast Cancer

Abstract: HER2-targeted anticancer therapies may be associated with cardiovascular adverse events. This study evaluated effects of the HER2-targeted antibody-drug conjugate trastuzumab deruxtecan (T-DXd, DS-8201a) on QT/QTc interval and its pharmacokinetics. Patients with heavily pretreated, metastatic HER2-expressing breast cancer were enrolled at seven study sites in Japan. T-DXd was administered intravenously at 6.4 mg/kg on day 1 of each 21day cycle. Primary end points were baseline-adjusted QTcF interval and pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Prolongation of corrected QT interval is known to be associated with fatal torsade de pointes arrhythmias. However, studies have revealed that both T-DM1 42 and T-DXd 57 did not have a clinically significant impact for the prolonged QTc interval remained below the safety threshold of 10 milliseconds. Our research revealed that ejection fraction decrease and congestive cardiac failure were the highest proportion of all-grade and serious CEs, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…Prolongation of corrected QT interval is known to be associated with fatal torsade de pointes arrhythmias. However, studies have revealed that both T-DM1 42 and T-DXd 57 did not have a clinically significant impact for the prolonged QTc interval remained below the safety threshold of 10 milliseconds. Our research revealed that ejection fraction decrease and congestive cardiac failure were the highest proportion of all-grade and serious CEs, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…Through manual retrieval, a total of 1437 articles were obtained, 523 articles were obtained after removing duplicates, 28 articles were obtained by checking the titles and abstracts of the articles, 12 articles [16][17][18][19][20][21][22][23][24][25][26][27] were finally included in the analysis by reading the full text. See Figure 1.…”
Section: Literature Screening and Characteristicsmentioning
confidence: 99%
“…8 studies [16][17][18][20][21][22][23]25] involving 642 people mentioned ORR, (I2=63.1%, p=0.008) indicating significant heterogeneity between studies. Figure 5 shows ORR in BC patients treated with T-DXd inhibitors [ES=0.57, 95% CI(0.50,0.64); P=0.000].…”
Section: Meta For Single-arm Study Orrmentioning
confidence: 99%
See 2 more Smart Citations